11+2+12+3+13+4++115+16=?     


Answer:

3

Step by Step Explanation:
  1. If we multiply the numerator and denominator of the first term by 21 we get:
    11+2=(21)(2+1)(21)=2121[Since, a2b2=(a+b)(ab)]=21
  2. Similarly, if we multiply numerator and denominator of the second term by 32, we get:
    12+3=32(3+2)(32)=3232[Since, a2b2=(a+b)(ab)]     =32
  3. Using the same technique with the other terms too, we can re-write the expression in question as:
    11+2+12+3+13+4++115+16=(21)+(32)+(43)++(1615)=1+16=1+4=3

You can reuse this answer
Creative Commons License